The influence of deliberate rumination on the post-traumatic growth of college students during the COVID-19 pandemic and the moderating role of self-efficacy - Xu, Yanhua; Yang, Guang; Liu, Luan; Wu, Xinyi (Frontiers in Public Health, 2023)
Objective To understand the relationship between deliberate rumination and post-traumatic growth and the mechanisms affecting this relationship, we constructed an adjustment model to test the impact of deliberate rumination on the post-traumatic growth of college students and the moderating role of self-efficacy during the 2019 COVID-19 pandemic. Study design and setting A total of 881 college students from a university of science and technology in Guangdong Province, China, completed a questionnaire that measured deliberate rumination, post-traumatic growth, and self-efficacy. SPSS (version 26) and the PROCESS plug-in (version 4.0) were used for correlation and moderation analyses. Results The correlation analysis showed that deliberate rumination was positively correlated with post-traumatic growth (r = 0.353, P < 0.01) and self-efficacy (r = 0.261, P < 0.01). Self-efficacy was also positively correlated with post-traumatic growth (r = 0.466, P < 0.01). In addition, we found that self-efficacy had a regulatory effect on the relationship between deliberate rumination and post-traumatic growth (R2 = 0.287, P < 0.001) and that this effect was significant. Conclusion The results show that deliberate rumination can be a positive predictor of post-traumatic growth and can play a certain role in fostering such growth. In addition, self-efficacy is a moderator that plays a buffer role between deliberate rumination and post-traumatic growth. These results contribute to a more comprehensive understanding of the mechanisms that affect post-traumatic growth.